Professores e Alunos: o engendramento da violência da escola - Silva, Marilda Da; Silva, Adriele Gonçalves Da (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2018)
Abstract: The school violence engendering is partially analyzed, considering the violence production in the school environment. This is a bibliographic research with quantitative and qualitative approach. Sources: 77 theses and 15 dissertations carried out in Brazil (2007 to 2012). Data collection and organization: Content Analysis. Main reference: Bernard Charlot and Pierre Bourdieu. Results: the sources showed that Brazilian teachers participate effectively in the school violence engendering, contributing to violence production in the school environment. The students are the main victims. The teacher is less affected by physical and verbal violence. The symbolic power is the most perpetrated by the teacher against the student. The school also plays a major role in it.

Resumo: Analisa-se o engendramento de uma face da violência da escola, tendo em vista a produção da violência em espaço escolar. Pesquisa bibliográfica quanti-qualitativa. Fontes: 77 dissertações e 15 teses produzidas no Brasil (2007 a 2012). Coleta e organização dos dados: Análise de Conteúdo. Fundamentação base: Bernard Charlot e Pierre Bourdieu. Resultados: as fontes apontaram que professores brasileiros são protagonistas na constituição da violência da escola, contribuindo para a produção da violência em espaço escolar. Os alunos são as principais vítimas dessa violência. O professor sofre menos violência física e verbal do que o aluno. A violência simbólica é a mais usada pelo professor contra o aluno. A escola também usa desse expediente.
Teachers and Students: the engendering of school violence
Keywords: Violence; School Violence; School Environment Violence; Teacher; Student; Violência; Violência da Escola; Violência em Espaço Escolar; Professor; Aluno